Zarządzanie bezpieczeństwem informacji - koncepcja i zastosowanie - Skowron, Paweł (Information security management - conception and use, 2006)
The synthetic expression of concept and structure of requirements of Information Security Management System (ISMS) consistent on BS 7799-2:2002 has been presented on the basis of constant improvement. The article also contains recommendations about the possibilities of implementing ISMS in organizations and its integration with quality management system based on ISO 9001:2000. In order to visualize the state of Information Security in Poland, a report prepared by a major advisory company has been used. The conclusion that can be drawn from the report is that Polish managers’ actions as far as ISMS is concerned are still non-systematic and temporary
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 305-313